Brain stem auditory evoked potentials in patients with multiple system atrophy with progressive autonomic failure (Shy-Drager syndrome). Issue 3 (March 1986) - Prasher, D; Bannister, R
Abstract : Brain stem potentials from three groups of patients, namely those with pure progressive autonomic failure, Parkinson's disease and multisystem atrophy with progressive autonomic failure (Shy-Drager syndrome) were compared with each other and a group of normal subjects. In virtually all the patients with multisystem atrophy with progressive autonomic failure the brain stem potentials were abnormal in contrast to normal findings with Parkinson's disease. The closely associated group of patients with progressive autonomic failure alone also revealed no abnormalities of the BAEP. This separation of the two groups, Parkinson's disease and progressive autonomic failure from multisystem atrophy with progressive autonomic failure is important clinically as multiple system atrophy of the Shy-Drager type has extra-pyramidal features closely resembling Parkinsonism or a late onset cerebellar degeneration. From the abnormalities of the brain stem response in multisystem atrophy with progressive autonomic failure, it is clear that some disruption of the auditory pathway occurs in the ponto-medullary region as in nearly all patients there is a significant delay or reduction in the amplitude of components of the response generated beyond this region. The most likely area involved is the superior olivary complex.